Health care and Christian ethics - Gill, Robin (Cambridge, UK ; New York : Cambridge University Press, 2006)
How can Christian ethics contribute significantly to health care ethics in today's Western, pluralistic society? Gill explores the healing stories in the Synoptic Gospels, identifying four core virtues present within them - compassion, care, faith and humility - that might bring greater depth to a purely secular interpretation of health care ethics.
Cover; Half-title; Series-title; Title; Copyright; Contents; Series editor's preface; Acknowledgements; Introduction; Chapter 1 Moral gaps in secular health care ethics; Chapter 2 Tensions in public theology; Chapter 3 Healing in the Synoptic Gospels; Chapter 4 Compassion in health care ethics; Chapter 5 Care in health care ethics; Chapter 6 Faith in health care ethics; Chapter 7 Humility in health care ethics; Conclusion; Bibliography of works cited; Index.
Includes bibliographical references (pages 215-224) and index.
Print version record.
Keywords: Medical ethics -- Religious aspects -- Christianity; Christian ethics; Christian ethics; Medical ethics -- Religious aspects -- Christianity; RELIGION -- Christian Theology -- Ethics; Christian ethics; Medical ethics -- Religious aspects -- Christianity; Electronic books